Culture in Advertisements: A Discursive and Semiotic Analysis of Maestro Pizza Advertisements in Saudi Arabia - Hajer Mohammed Albogami; Nuha Alshurafa; Tariq Elyas; Maather Alrawi (WISE Pendidikan Indonesia, 2025)
Advertisements have long been acknowledged not merely as tools for product promotion but as powerful cultural agents that reflect and shape societal values. This study critically examines the cultural and ideological underpinnings embedded in Maestro Pizza advertisements aired on Saudi National Days 88, 89, and 91. Employing Fairclough’s Critical Discourse Analysis (CDA) and Barthes’ Semiotic Theory, this research investigates twelve selected visual frames from three advertisements to uncover how Saudi cultural identities, historical figures, and social norms are represented. The findings highlight the prominence of cultural symbols such as national landmarks, historical narratives, and the evolving image of Saudi women, illustrating how these advertisements align with national ideologies and social conventions. This study underscores the significance of advertising as a medium for cultural transmission, offering new insights into how advertisements can reflect and perpetuate national identity in the context of Saudi Arabia. The implications of these findings contribute to the broader field of media studies and cultural representation in advertising.